Tracking and taxing the super-rich: Insights from Swiss rich lists - Enea Baselgia; Isabel Z. Martínez (ETH Zurich, KOF Swiss Economic Institute, 2022)
We collect, digitize, and supplement the Swiss rich list for the years 1989-2020 published in the "BILANZ" business magazine to gain new insights on the structure and dynamics of top wealth in Switzerland. Using this data allows us study the the super-rich in Switzerland in ways that were not possible in previous research based largely on tax data. In addition to making this valuable data source accessible for future research, and also discussing its limitations, we make three distinctive contributions to the literature. First, we present a number of new facts on the wealth elite in Switzerland. We show that about 60% of the super-rich are heirs-a much larger fraction than in the United States where many of the super-rich are self-made-and that five in ten super-rich residing in Switzerland are foreignborn. Second, we estimate the sensitivity of the location-decision of super-rich foreigners to a preferential tax scheme that offers wealthy foreigners to be taxed on their expenses rather than on their true income and wealth. We are the first to evaluate this policy-similar to "non-dom" taxation that exists in other countries like the UK or Italy-and show that when some of the Swiss cantons abolished this practice, they lost about 30% of their stock of super-rich taxpayers. Third, we use the wealth series compiled in our BILANZ dataset to estimate the wealth shares of the top 0.01% in Switzerland and show how they compare to earlier estimates by Föllmi and Martínez (2017) based on wealth tax data. We find that top wealth concentration is higher than previously assumed, an conclude that top wealth shares based on tax data constitute a lower bound, while the estimates based on our BILANZ data are upper bounds.
hdl:20.500.11850/534627
Keywords: D31; H24; C81; 330; super-rich; wealth inequality; wealth distribution; wealth mobility; top wealth shares